PHYTOCHEMICALS AS POTENTIAL INHIBITORS OF LANOSTEROL 14 Α-DEMETHYLASE (CYP51) ENZYME: AN IN SILICO STUDY ON SIXTY MOLECULES - JADHAV, ASHWINI KHANDERAO; KHAN, PATHAN KAMRAN; KARUPPAYIL, SANKUNNY MOHAN (International Journal of Applied Pharmaceutics, 2020)
Lanosterol 14 α-demethylase (CYP51) is a key protein involved in ergosterol biosynthesis of Candida albicans and a crucial target for ergosterol synthesis inhibition. However, in the last two decades drug resistance is reported under clinical situations to most of the prescribed antifungal drugs like azole group of drugs. In this study, molecular docking of sixty plant molecules with Lanosterol 14 α-demethylase protein has been done. The homology modeling tool PHYRE2 was used to predict the structure of Lanosterol 14 α-demethylase. Predicted structure was used for docking studies with sixty plant molecules by using Autodock 1.5.6 cr2™. Among the sixty plant molecules, forty-seven were found to form hydrogen bond and the rest of the plant molecules did not form a hydrogen bond with Lanosterol 14 α-demethylase. Docking study of a library of sixty molecules revealed that 48 plant molecules showed an excellent and good binding affinity with predicted protein model Lanosterol 14 α-demethylase of Candida albicans. The binding residue comparison of docked molecules with that of Ketoconazole revealed, fourteen molecules have similar binding residue. These fourteen molecules may have a similar mode of action as that of Ketoconazole. These molecules should be screened and used to discover new antifungal therapeutic drugs.